2021
DOI: 10.1002/essoar.10504352.2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Meta-analysis of Cryogenian through modern quartz microtextures reveals sediment transport histories

Abstract: Quantitative scanning electron microscopy (SEM) quartz microtextural analysis can reveal the transport histories of modern and ancient sediments. However, because workers identify and count microtextures differently, it is difficult to directly compare quantitative microtextural data analyzed by multiple workers. As a result, the defining microtextures of certain transport modes and their probabilities of occurrence are not well constrained. We used principal component analysis (PCA) to directly compare modern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…The probability of high-stress microtextures occurring that reflect microstriae, such as grooves and troughs, is extremely low in eolian systems far removed from modern or Pleistocene glaciation (Reahl et al, 2021). Moreover, samples collected in fluvial systems far removed from a glacial influence yielded very low probabilities of retaining a high-stress signal (Reahl et al, 2021). Thus, while high-stress microtextures have been reported from deposits other than those of glacial origin, most of the reported occurrences are associated with glaciation.…”
Section: Quartz-grain Microtexturesmentioning
confidence: 98%
See 4 more Smart Citations
“…The probability of high-stress microtextures occurring that reflect microstriae, such as grooves and troughs, is extremely low in eolian systems far removed from modern or Pleistocene glaciation (Reahl et al, 2021). Moreover, samples collected in fluvial systems far removed from a glacial influence yielded very low probabilities of retaining a high-stress signal (Reahl et al, 2021). Thus, while high-stress microtextures have been reported from deposits other than those of glacial origin, most of the reported occurrences are associated with glaciation.…”
Section: Quartz-grain Microtexturesmentioning
confidence: 98%
“…Percussion microtextures consist of v-shaped cracks and edge rounding, and are common to eolian, coastal, and fluvial systems. High-stress microtextures consist of grooves, troughs, and gouges (Figure 1) resulting from grain-to-grain contact under sustained shear stress and are common in grains recovered from till and proglacial deposits (Mahaney and Kalm, 1996;Hart, 2006;Sweet and Brannan, 2016;Smith et al, 2018;Kalinska et al, 2021;Reahl et al, 2021), but also are reported from structural shear zones and debris flows (Mahaney, 2002). Polygenetic microtextures are the remainder of the mechanically induced microtextures observable on grain surfaces and originate through various processes.…”
Section: Quartz-grain Microtexturesmentioning
confidence: 99%
See 3 more Smart Citations